Identification of a novel opioid, N-piperidinyl etonitazene (etonitazepipne), in patients with suspected opioid overdose. (2nd September 2022) - Calello, Diane P.; Aldy, Kim; Jefri, Mohamed; Nguyen, Tuyet-Anh T.; Krotulski, Alex; Logan, Barry; Brent, Jeffrey; Wax, Paul; Walton, Sara; Manini, Alex F.
Abstract: Background: Novel opioids in the illicit drug supply, such as the "nitazene" group of synthetic opioids, present an ongoing public health problem due to high potency and respiratory depressant effects. We describe three patients in whom N -piperidinyl etonitazene, a compound not previously reported in human exposure, was detected after suspected opioid overdose. Other substances that these patients tested for included fentanyl, cocaine, levamisole, phenacetin, benzoylecgonine, para -fluorofentanyl, presumptive heroin (tested as 6-monoacetylmorphine (6-MAM), morphine, and codeine), and tramadol. Methods: This is a case series of patients with acute opioid overdose enrolled in an ongoing multicenter prospective cohort study. Data collected included reported substance use, clinical course, naloxone dose and response, outcome, and analytes detected in biological samples. Results: Between October 6, 2020 and October 31, 2021, 1006 patients were screened and 412 met inclusion criteria. Of these, three patients (age 33–55) tested positive for N -piperidinyl etonitazene at one site in New Jersey over a period of three days in July 2021. Two patients reported the use of cocaine; one reported the use of heroin and alprazolam. All three patients received naloxone with improvement in their mental status (2 milligrams (mg) intranasally (IN); 8 mg IN; 0.08 mg intravenous (IV)). Two of three received subsequent doses for recurrence of opioid toxicity (0.4–0.6 mg IV). One patient was diagnosed with pneumonia and admitted to the intensive care unit, one was discharged from the Emergency Department (ED), and one used additional drug while in the ED and required admission for a naloxone infusion. None developed organ damage or sequelae. Conclusion: These cases represent a local outbreak of a novel "nitazene" opioid. Public health toxicosurveillance should incorporate routine testing of this emerging class of synthetic compounds in the illicit drug supply.